Differential deletion of GDNF in the auditory system leads to altered sound responsiveness - Harasztosi, Csaba; Wolter, Steffen; Gutsche, Katja; Durán‐Alonso, María Beatriz; López‐Hernández, Iris; Pascual, Alberto; López‐Barneo, José; Knipper, Marlies; Rüttiger, Lukas; Schimmang, Thomas (Journal of neuroscience research, 2020)
Glial‐derived neurotrophic factor (GDNF) has been proposed as a potent neurotrophic factor with the potential to cure neurodegenerative diseases. In the cochlea, GDNF has been detected in auditory neurons and sensory receptor cells and its expression is upregulated upon trauma. Moreover, the application of GDNF in different animal models of deafness has shown its capacity to prevent hearing loss and promoted its future use in therapeutic trials in humans. In the present study we have examined the endogenous requirement of GDNF during auditory development in mice. Using a lacZ knockin allele we have confirmed the expression of GDNF in the cochlea including its sensory regions during development. Global inactivation of GDNF throughout the hearing system using a Foxg1‐Cre line causes perinatal lethality but reveals no apparent defects during formation of the cochlea. Using TrkC‐Cre and Atoh1‐Cre lines, we were able to generate viable mutants lacking GDNF in auditory neurons or both auditory neurons and sensory hair cells. These mutants show normal frequency‐dependent auditory thresholds. However, mechanoelectrical response properties of outer hair cells (OHCs) in TrkC‐Cre GDNF mutants are altered at low thresholds. Furthermore, auditory brainstem wave analysis shows an abnormal increase of wave I. On the other hand, Atoh1‐Cre GDNF mutants show normal OHC function but their auditory brainstem wave pattern is reduced at the levels of wave I, III and IV. These results show that GDNF expression during the development is required to maintain functional hearing at different levels of the auditory system. Deficiency of GDNF in cochlear hair cells (Atoh1‐Cre) reduces inner hair cell (IHC)/cochlear output, although outer hair cell (OHC) function is normal. Deficiency of GDNF in cochlear neurons (TrkC‐Cre) leads to increased OHC and IHC/auditory nerve responses. Tissue‐specific GDNF expression during development is thus required to maintain normal hearing.